Religiosity and happiness inter generation of labor in Indonesia - Mustofa Mustofa (Journal of Social Studies (JSS), 2022)
If people are religious, are they happier? This study tries to answer the preceding question and to determine the factors affecting happiness among Indonesian labor. The dummy generation variable was used to know whether Gen X, Gen Y, and baby boomers can affect happiness. Several variables were also examined related to happiness. This study can be categorized as empirical research using ordinary least squares. The data were sourced from the Indonesian Family Life Survey 2014 (IFLS5). The number of samples selected was 21,919 individuals with the criteria of individuals aged 15 years and over who worked and earned income. The data analysis technique used OLS regression to prove the factors that influence happiness. The results of the research showed that religiosity, education, ownership of assets, social, job satisfaction, and the dummy generation have a positive and significant effect on people’s happiness. This study has confirmed that religiosity is a factor that can affect people’s happiness. Another factor, the generation the person belongs to, also affects happiness.